Lower 90-day Hospital Readmission Rates for Esophageal Variceal Bleeding After TIPS: A Nationwide Linked Analysis. Issue 1 (January 2020) - Rush, Barret; Deol, Navjot; Teriyaki, Anour; Sey, Michael; Jairath, Vipul; Walley, Keith R.; Celi, Leo A.; Brahmania, Mayur
Abstract : Objective: Hospital readmission rates following a transjugular intrahepatic portosystemic shunt (TIPS) insertion after an episode of esophageal variceal bleeding (EVB) has not been well studied. We aimed to address this gap in knowledge on a population level. Methods: The Nationwide Readmission Database (NRD) was used to study the readmission rates for patients with decompensated cirrhosis who had a TIPS insertion performed for EVB. The NRD is a national database that tracks patients longitudinally for hospital readmissions. A propensity score matching model was created to match patients who received TIPS with those who did not. Results: A total of 42, 679, 001 hospital admissions from the 2012 to 2014 NRD sample were analyzed. There were 33, 934 patients with EVB who met inclusion criteria for the study, of whom, 1527 (4.5%) received TIPS after EVB and were matched with 1527 patients with EVB who did not undergo TIPS. With a uniform follow-up of 3 months, patients with TIPS were less likely to be readmitted to hospital with a recurrent EVB [odds ratio (OR): 0.33, 95% confidence interval (CI): 0.24-0.47, P <0.01], although were more likely to be readmitted with hepatic encephalopathy (OR: 1.66; 95% CI: 1.31-2.11, P <0.01). At 3 months, there was no difference in all cause hospital readmission rate between the 2 groups (OR: 38.8%; 95% CI: 38.1-44.9 TIPS vs. OR: 41.5%; 95% CI: 34.1-43.3 non-TIPS: P =0.17). Conclusions: In this large nationally representative study, TIPS insertion after an episode of EVB was associated with a significantly lower risk of 3-month readmission for recurrent EVB compared with patients who did not receive TIPS. Although those receiving TIPS had a higher rate of hepatic encephalopathy the overall readmission remained unchanged.